Genetic and phenotypic heterogeneity suggest therapeutic implications in SCN2A-related disorders - Wolff, Markus; Pietz, Joachim; Moog, Ute; Korenke, Christoph (Brain, 2017)
SCN2A mutations have been described in a wide range of epilepsies. Wolff et al showed that early onset epilepsies are caused by missense mutations, displaying G